2012
DOI: 10.3389/fneur.2012.00011
|View full text |Cite
|
Sign up to set email alerts
|

High Prevalence of Chronic Pituitary and Target-Organ Hormone Abnormalities after Blast-Related Mild Traumatic Brain Injury

Abstract: Studies of traumatic brain injury from all causes have found evidence of chronic hypopituitarism, defined by deficient production of one or more pituitary hormones at least 1 year after injury, in 25–50% of cases. Most studies found the occurrence of posttraumatic hypopituitarism (PTHP) to be unrelated to injury severity. Growth hormone deficiency (GHD) and hypogonadism were reported most frequently. Hypopituitarism, and in particular adult GHD, is associated with symptoms that resemble those of PTSD, includin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
78
0
5

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 138 publications
(88 citation statements)
references
References 115 publications
5
78
0
5
Order By: Relevance
“…[1][2][3][4][5] Recently, pituitary dysfunction has been shown to be a consequence of bTBI in soldiers returning from war, [5][6][7] with evidence suggesting that bTBI can cause impairment of hypothalamicpituitary pathways. 8 Further, it has been hypothesized that altered pituitary function may lead to cognitive and neuropsychiatric dysfunction.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4][5] Recently, pituitary dysfunction has been shown to be a consequence of bTBI in soldiers returning from war, [5][6][7] with evidence suggesting that bTBI can cause impairment of hypothalamicpituitary pathways. 8 Further, it has been hypothesized that altered pituitary function may lead to cognitive and neuropsychiatric dysfunction.…”
mentioning
confidence: 99%
“…11,12 GH deficiency and ACTH dysfunction have been related to cognitive deficiencies following TBI and can lead to symptoms such as fatigue, anxiety, irritability, insomnia, sexual dysfunction, and decreased quality of life. 3 Tümer and colleagues 14 reported on increased hypothalamic expression of oxidative stress and activation of the sympathoadrenal medulla at an acute time-point of 6 h following blastinduced neurotrauma (BINT) in rats. 13 This study demonstrated that exposure to blast was associated with increased biosynthesis of catecholamine in the brain and elevated levels of stress-related biomarkers in serum.…”
mentioning
confidence: 99%
“…This pattern of deficiency following TBI makes sense, because the cells that produce GH and gonadotropins (the somatotrophs and gonadotrophs, respectively) are arguably more vulnerable to damage because of their location in the lateral wings of the pituitary, which only have one blood supply [31]. GH and gonadotropin are hormones that are of great interest in the discussion of performance enhancing drugs, because of the role of GH in building body mass, and the role of the gonadotropins in producing testosterone.…”
Section: The Effects Of Hormone Deficiency and Hormone Replacement Thmentioning
confidence: 98%
“…The two hormones deficiencies that are most frequently related to TBI are GH deficiency and gonadotropin deficiency [31]. This pattern of deficiency following TBI makes sense, because the cells that produce GH and gonadotropins (the somatotrophs and gonadotrophs, respectively) are arguably more vulnerable to damage because of their location in the lateral wings of the pituitary, which only have one blood supply [31].…”
Section: The Effects Of Hormone Deficiency and Hormone Replacement Thmentioning
confidence: 98%
“…Ancak, kafa travması sonucu oluşan hasardan sadece primer hasar sorumlu değil-dir. Primer doku hasarını takiben ortaya çıkan birçok karmaşık fi zyopatolojik olaya bağlı olarak sekonder hasar da oluşmaktadır [3][4][5] . Beyin hasarında rol oynayan Travmatik beyin hasarına (TBH) bağlı hipofi z hormon bozuklukları genellikle nonspesifi k belirtiler ile seyretmektedir ve bu nedenle tanı gecikebilir.…”
Section: Girișunclassified